Pengaruh Pemberian Beberapa Jenis Herbisida Terhadap Pertumbuhan Dan Hasil Tanaman Padi (Oryza Sativa L.) Dengan Sistem Tanam Tabur Benih Langsung Tanpa Olah Tanah (Tabelatot) - I MADE KRISNA WIDYASMARA; I WAYAN PASEK ARIMBAWA; I KETUT ARSA WIJAYA (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2019)
The effect ot the type of herbicide to controlling weeds and the increasing thegrowth and yield of rice plants in tabelaltot planting system. Rice plants are the most important crop cultivation because most of the population makes rice as a staple food. Efforts to support the fulfillment of rice needsare made by maintaining rice productivity. Increased rice productivity is currently stillexperiencing obstacles such as in improper crop cultivation techniques and problemsin weed control, therefore proper weed cultivation and control techniques need to beassessed. The purpose of this research was to find out the type of herbicide that is mosteffective in controlling weeds and can increase the growth and yield of rice plants intabelaltot planting system. This study used a randomized block design (RCBD) with4 treatments, namely control (without herbicide treatment), logran herbicide,metafuron herbicide and benfuron herbicide. The treatment was repeated six times.The results showed that the herbicide treatment significantly affected the weight of thedried grain harvest compared with control. Logran herbicide treatment showed thehighest dry grain weight of ha-1 harvest was 8.38 tons / ha-1 and significantly differentfrom the control of 6.00 tons / ha-1, the high yield was due to the ability of logranherbicide that could suppress growth of the highest weeds, namely 77% compared toherbicides metafuron namely 57% and benfuron namely 56% and significantlydifferent compared to controls, the competition that occurred between rice plants andweeds in logran herbicide treatment was less so that it made yields increase.